Effect of phosphoric acid concentration and anodizing time on the properties of anodic films on titanium - Torres, Dimas L. [UNESP]; Pereira, Marinalda C. [UNESP]; Silva, José W. J. [UNESP]; Codaro, Eduardo N. [UNESP]; Acciari, Heloisa A. [UNESP] (My University, 2015)
In this study, it was investigated the influence of electrolyte concentration and anodizing time on the electrochemical behaviour and morphology of anodic films formed on commercially pure Ti. Electrochemical methods and surface analyses were used to characterize the films. It was found that the electrolyte concentration and anodizing time affect the growth and protective characteristics of films in a physiologic medium. It was possible to observe their non-uniformity on Ti substrates under the tested conditions. In potentiodynamic profiles, it was observed that passivation current values are affected by an anodizing time increase. Variations in impedance spectra were associated with an increase of defects within the film.
Keywords: Anodic films; Anodizing; Biomedical implants; Chloride medium; Titanium